2013
DOI: 10.1021/jp400333z
|View full text |Cite
|
Sign up to set email alerts
|

Multinuclear Solid State Nuclear Magnetic Resonance Investigation of Water Penetration in Proton Exchange Membrane Nafion-117 by Mechanical Spinning

Abstract: (1)H, (17)O, and (19)F solid state NMR spectroscopies have been used to investigate water penetration in Nafion-117 under mechanical spinning. It is found that both (1)H and (17)O spectra depend on the orientation of the membrane with respect to the magnetic field. The intensities of the side chain (19)F spectra depend slightly on the orientation of membrane with respect to the magnetic field, but the backbone (19)F spectra do not exhibit orientation dependence. By analyzing the orientation dependent (1)H and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…In addition, individual water and methanol resonances were resolved even at slower 1 kHz MAS spinning, and for the ATMPP (IEC = 1.48) membrane static PFG NMR diffusion experiments revealed a biexponential decay for the water environment with diffusion rates on the same order of magnitude as those obtained using PFG HRMAS NMR. This does not fully dismiss the effects of MAS centrifugation as the membranes, as the multiple broad overlapping resonances observed for the water or methanol environments in the TMAC 6 PPC 6 membranes (Figure 1) are very similar in appearance to those reported during the Nafion study, 36 and warrant further investigations.…”
Section: ■ Experimental Sectionmentioning
confidence: 78%
See 2 more Smart Citations
“…In addition, individual water and methanol resonances were resolved even at slower 1 kHz MAS spinning, and for the ATMPP (IEC = 1.48) membrane static PFG NMR diffusion experiments revealed a biexponential decay for the water environment with diffusion rates on the same order of magnitude as those obtained using PFG HRMAS NMR. This does not fully dismiss the effects of MAS centrifugation as the membranes, as the multiple broad overlapping resonances observed for the water or methanol environments in the TMAC 6 PPC 6 membranes (Figure 1) are very similar in appearance to those reported during the Nafion study, 36 and warrant further investigations.…”
Section: ■ Experimental Sectionmentioning
confidence: 78%
“…There are concerns about the possibility of the free-solvent environments arising from the penetration of water and methanol into the polymer membrane due to centrifugal forces. A recent study showed that water migrates into Nafion membranes during MAS spinning, probing polymer environments not normally accessible to water penetration . This water penetration occurred mainly at high MAS speeds (12 kHz) or extended periods of spinning.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation